2016
DOI: 10.1136/bmjstel-2015-000089
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing simulation-based clinical training: comparing the concurrent validity of students' self-reported satisfaction and confidence measures against objective clinical examinations

Abstract: IntroductionSimulation-based education (SBE) literature is replete with student satisfaction and confidence measures to infer educational outcomes. This research aims to test how well students' satisfaction and confidence measures correlate with expert assessments of students' improvements in competence following SBE activities.MethodsN=85 paramedic students (mean age 23.7 years, SD=6.5; 48.2% female) undertook a 3-day SBE workshop. Students' baseline competence was assessed via practical scenario simulation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…On the other hand this results are congruent with (Jefferies, 2007) which suggests that the outcomes of satisfaction and self-confidence are due to combination of factors related to demographic characteristics. Also the study carry by (Carter, et al, 2015) reported that there was statistical significantly between baseline and post workshop (35.7%→53.4%, p<0.001), as did students' confidence (55.7%→60.5%, p<0.001), and their workshop satisfaction was high (71.0%). Satisfaction and post workshop confidence measures were moderately correlated (r=0.377, p=0.001).…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand this results are congruent with (Jefferies, 2007) which suggests that the outcomes of satisfaction and self-confidence are due to combination of factors related to demographic characteristics. Also the study carry by (Carter, et al, 2015) reported that there was statistical significantly between baseline and post workshop (35.7%→53.4%, p<0.001), as did students' confidence (55.7%→60.5%, p<0.001), and their workshop satisfaction was high (71.0%). Satisfaction and post workshop confidence measures were moderately correlated (r=0.377, p=0.001).…”
Section: Discussionmentioning
confidence: 93%
“…Abe, Y et al (e.g., Abe, Y et al, 2013 ) used the teamwork activity inventory to assess students’ non-technical skills. Meanwhile, some scholars pointed out that satisfaction and confidence are valid indicators for measuring the teaching of scenario-based simulations (e.g., Carter, O et al, 2016 ). While domestic scholars Guo S. Y et al (e.g., Guo S. Y et al, 2022 ) used a fuzzy comprehensive evaluation method to assess the teaching quality of nursing scenario simulation practical training.…”
Section: Discussionmentioning
confidence: 99%
“…Overall student perceptions of benefit were particularly strong in the areas of communication, efficiency and teamwork and meet the outcomes identified by Carter et al (2016 p. 30) that ‘student satisfaction and improvements in confidence are highly desirable educational outcomes from a pedagogical perspective.’3 …”
Section: Discussionmentioning
confidence: 99%